Effect of an “Autogenous Leukocyte Platelet-Rich Fibrin Tooth Graft” Combination around Immediately Placed Implants in Periodontally Compromised Sites: A Randomized Clinical Trial - Walid ElAmrousy; Dalia Rasheed Issa (International Journal of Dentistry)
Objective. Autogenous tooth bone graft (ATBG) was suggested as a source for bone grafting materials, especially as they have similar chemical composition to bone. This study goal was to assess the clinical and radiographic consequences of ATBG with or without L-PRF on bone deposition around immediate implants placed in periodontally hopeless sites. Materials and Methods. 26 patients, with periodontally diseased teeth, underwent random assignment to receive the surgical protocol either with L-PRF over ATBG around immediately inserted implants (test group) or without it (control group). Clinical examination was observed. Radiographically, bone changes horizontally and vertically to determine marginal bone loss (MBL) and mesiodistal bone changes were made at the base line and 6 and 9 months after implant insertion. Statistical analysis utilizing paired Student's t-test was used for comparing results within the same group, whereas an independent-sample t-test was used for intergroup variable comparison. Results. All implants met the criteria of success without any complications at the follow-up period. Nonsignificant differences were detected between horizontal bone alterations in both groups at 6 and 9 months P>.001. The test group showed statistically significant lower MBL than the control group P<.001. The mesiodistal bone gain in the test group was significantly higher than that of the control group at the 6-month period P<.001. The mesiodistal bone loss in the control group was significantly higher than that of the test group at the 9-month period P<.001. Conclusion. The ATBG- L-PRF combination therapy enhances new bone formation and appeared to be a favorable procedure with immediate implant placement, particularly in severe periodontitis cases.